New Approach in Analyzing Risk Level of Flood in Tropical Region: A Case Study at Pahang River Basin, Malaysia - Ismail, Aqilah; Shakir Mohd Saudi, Ahmad; Khairul Amri Kamarudin, Mohd; Hafiz Md Saad, Muhammad; Azid, Azman; Surayya Mohd Saudi, Nur; Mahmud, Muaz (International Journal of Engineering and Technology, 2018)
This study focuses on flood risk recognition factor that leads to major contribution of floods in Pahang River basin, identify the correlation between variables and determine factor that influence the flood risk pattern in Pahang. Four hydrological variables been applied. Chemometric technique of Principal Component Analysis (PCA) method and Statistical Process Control (SPC) method were being applied to identify the main contributor for flood, predicting hydrological modeling and risk of flood occurrence at Pahang river basin. Findings from Principal Component Analysis (PCA) confirmed that all selected variables were significant. The relationship between Suspended Solid and Stream Flow with Water Level were very high with correlation of coefficient value more than 0.7. SPC set up a new control limit for all variables. Data beyond the Upper Control Limit (UCL) value is considered as high risk for flood occurrence. Most of the trend pattern showed in year 2007 as high peak. Rapid development growth and anthropogenic activities caused the sediment of Suspended Solid triggered the Water Level and Stream Flow to arise than normal level. Thus, local authority should take earlier precaution for flood prevention and emergency responses plan at the study area for any development of land by takes obligatory action to the developers especially those development that arise along river channel.Â